Pengaruh Perhatian Orang Tua Terhadap Hasil Belajar Matematika Siswa Kelas VI SD Negeri 122368 Kota Pematang Siantar T.A 2023/2024 - Sosial Indah G. Sinambela; Arifin Siregar; Daitin Tarigan; Erlinda Simanungkalit; Putra Afriadi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The purpose of this research are 1) To determine the attention of parents of class VI students at SD Negeri 122368 Pematang Siantar T.A 2023/2024, 2) To determine the mathematics learning outcomes of class VI students at SD Negeri 122368 Pematang Siantar T.A 2023/2024, 3) To determine the effect of attention parents on the mathematics learning outcomes of class VI students at SD Negeri 122368 Pematang Siantar T.A 2023/2024. This type of research is quantitative research with an ex post facto method. This research sample used total sampling, namely all class VI students, totaling 35 students, consisting of 15 male students and 20 female students. Data collection in this research was carried out using questionnaires and documentation. The data analysis technique used is a simple linear regression test and a significant test (t test). The results of the research show that there is a significant influence between parental attention (X) on mathematics learning outcomes (Y) of class VI students at SD Negeri 122368 Pematang Siantar T.A 2023/2024. This is proven by the tcount value for the parental attention variable (X) of 6.287 while the ttable value is 1.69236, so tcount > ttable (6.287 > 1.69236), with a sig value α = 0.00 < 0.05 so it can be stated that Ho is rejected and Ha is accepted. Variable contribution.